Perencanaan Enterprise Architecture pada Perusahaan Manufactur PT. X - Jodjana, Maximillian; Rostianingsih, Silvia; Santoso, Leo Willyanto (Jurnal Infra, 2016)
PT. X is a company engaged in the field of industrial coating steel with aluminum, zinc, and silicon, known as BJLAS with brand name zinium. Information systems owned by PT. X has not been fully integrated because there are recording data or information that is done manually. Therefore, through this thesis will be analyzes the design and manufacture of enterprise information systems architecture for companies using Enterprise Architecture Planning method. Begins with the analysis of business models and business strategies that exist in the company by looking at the condition of the existing information technology as well as the problems and needs of information technology in the future. After that it will be making design data architecture, application architecture and technology architecture in accordance with the companys business strategy and process. System which already exists and is used by the company are for the sale, purchase, and production process. The result data of architecture for company consists of several sub-systems, namely Sub Systems Marketing and Sales, Sub Systems Purchasing, Production Systems Sub, Sub Systems Personnel, Finance and Accounting Sub System. Application architecture consists of main application like information systems Marketing and Sales, Purchasing Information System, Production Information System, Human Resources Information Systems, Finance and Accounting Information Systems. Each application is an application created using Visual Basic base that had been used the previous company. And supporting applications like Data Provider that helps the main application to request the required data from other applications. The technology architecture that used is the Client / Server Architecture and Service Oriented Architecture Pattern.